2008
DOI: 10.1007/s10800-008-9706-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical polymerisation of phenol in aqueous solution on a Ta/PbO2 anode

Abstract: This paper deals with the treatment of aqueous phenol solutions using an electrochemical technique. Phenol can be partly eliminated from aqueous solution by electrochemically initiated polymerisation. Galvanostatic electrolyses of phenol solutions at concentration up to 0.1 mol dm -3 were carried out on a Ta/PbO 2 anode. The polymers formed are insoluble in acidic medium but soluble in alkaline. These polymers were filtered and then dissolved in aqueous solution of sodium hydroxide (1 mol dm -3 ). The polymers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 30 publications
5
38
0
1
Order By: Relevance
“…Cyclic voltammetry and chronoamperometry were performed at different temperatures (25,40,60,75, and 85°C) in aqueous solution containing 1 mol L -1 of sulfuric acid and 1 or 4 mmol L -1 of phenol. Chronoamperometric measurements were carried out at constant potentials chosen either in the region of water stability or oxygen evolution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyclic voltammetry and chronoamperometry were performed at different temperatures (25,40,60,75, and 85°C) in aqueous solution containing 1 mol L -1 of sulfuric acid and 1 or 4 mmol L -1 of phenol. Chronoamperometric measurements were carried out at constant potentials chosen either in the region of water stability or oxygen evolution.…”
Section: Methodsmentioning
confidence: 99%
“…Results of bulk electrolysis conducted on Ta/bPbO 2 at high anodic current density and high temperature have shown that 39% of the starting phenol was removed as polymer under the best operating conditions [39,40]. It was also shown that the fraction of starting phenol converted into polymers increased substantially with temperature and that no electrode passivation (in that no noteworthy tensioncell increase happened) was observed over electrolysis [40].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The main advantage in proceeding by electropolymerisation is the low consumption of the electric charge compared with electrochemical mineralisation [1]. In this way, the removal of phenols from aqueous solutions by electrochemical polymerisation was conducted on granular activated carbon [2], carbon fibre [3], Ta/␤-PbO 2 [1,4] and polyaniline/glassy carbon electrodes [5]. Nevertheless, electropolymerisation of phenolic compounds leads to the deposition of a non-conductive film that blocks the electrode activity and prevents further removal of phenol [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of our previous works [1,4,20,21] was to find the operating conditions that allow electropolymerisation to proceed as long as a current is supplied to the electrode; thus, the polymeric film inevitably deposited on the electrode surface must have the highest permeability for phenol molecules. The main operating conditions were described in Ref.…”
Section: Introductionmentioning
confidence: 99%